The effect of IVM and IVC media on in vitro development of bovine embryos - Mergawati, E.T; Kaiin, E.M; Eriani, K; Yanthi, N.D; ., Indriawati (Indonesian Journal of Animal and Veterinary Sciences, 2000)
The purpose of this study was to examine the effect of medium combination of IVM and IVC on the in vitro development of bovine embryos. The study involved 4 groups in a 2 (IVM medium) x 2 (IVC medium) factorial in a randomized block design. Each group was replicated for 5 times. The treatments were as follows: TCM-199/CR1aa (T1); TCM-199/SOF (T2); B- 199/CR1aa (T3) and B-199/SOF (T4). Oocytes were aspirated from ovaries collected at local abattoirs using aspiration medium of PBS supplemented with 3% FCS and 0.1% Penicillin and Streptomycin. The oocytes were matured in medium of TCM-199 or B-199 supplemented with 10% FCS, hormones: 10Î¼g/ml FSH+ 10Î¼g/ml hCG+ 1Î¼g/ml Estradiol. Maturation was maintained at 37oC for 22 hours in 5% CO2 incubator with high humidity. A method of BRACKETT & Oliphant (BO) was used to fertilize the matured oocytes. The fertilization was incubated for 7 hours in the 5% CO2 incubator. Two culture media of CR1aa or SOF/AA/BSA were used to develop the fertilized oocytes undergo to morula and blastocyst embryos. The findings showed that the proportion of oocytes cleaved and formation of blastocysts were affected significantly by a combination of IVM and IVC media (P<0.05). A combination of B-199/SOF (T4) resulted in a higher blastocyst rate (32%) than others (T3= 29%; T2=T1= 23%). This study suggests that either SOF/AA/BSA or CR1aa has similar competence in development of bovine embryos in vitro. Â  Key words: Bovine embryo, IVF, maturation medium, culture medium